Design and Meshing Analysis of 3-DOF Spherical Gears and Ring Racks - Liang Yong; Gu Peng; Gao Jianjun; Zhang Litong; Wang Baichao (Jixie chuandong)
A ring rack meshing with a 3-DOF spherical gear was proposed. The ring rack was composed of two ring-shaped rack tooth surfaces and two spherical tooth surfaces. It can realize the movement and rotation between the plane and the sphere, and theoretically there is no transmission error. According to the meshing principle of the spherical gear and the ring rack, the tooth surface equation and the meshing equation of the ring rack were deduced by using the space transformation theory. Then, according to the structural characteristics of the ring rack, the number of teeth of each layer of the ring rack when meshing with the spherical gear was deduced from the correct meshing conditions of the spherical gear and the arc-shaped teeth of the ring rack. Finally, the kinematics simulation of the ring rack and the meshing efficiency of each layer of the ring rack were calculated, which verified that the structure can transmit power stably. The parametric design of the ring rack provides a structure that enables the conversion of motion and power between the plane and the sphere.